Anticipatory effects of the implementation of the Chilean Law of Food Labeling and Advertising on food and beverage product reformulation. (27th June 2019) - Kanter, Rebecca; Reyes, Marcela; Vandevijvere, Stefanie; Swinburn, Boyd; Corvalán, Camila
Summary: This study evaluated the anticipated food and beverage product reformulation by industry before the Chilean Law of Food Labeling and Advertising (Law 20.606) was implemented in June 2016 requiring a front‐of‐package (FOP) warning label for products high in sodium, total sugars, saturated fats, and/or total energy. Fieldworkers photographed a purposive sample of packaged food and beverage products in February 2015 (n = 5421) and February 2016 (n = 5479) from six different supermarkets in Santiago, Chile. The same products collected in both years (n = 2086) from 17 food and beverage categories with added critical nutrients (nutrients of concern: sodium, total sugars, and saturated fats) were included in this longitudinal study. The average change in energy and critical nutrient content was estimated by category. The number of warning labels potentially avoided because of reformulation was determined. Between February 2015 and February 2016, no category experienced reductions > 5% average change in energy or critical nutrient content; and some increased in critical nutrient content. Few products (<2%) would have avoided at least one warning label with reformulation. In a diverse sample of food and beverage products, there was minimal reformulation by industry in anticipation of the implementation of the 2016 Chilean Law of Food Labeling and Advertising.